Ballet in writing: precepts and rules of composition for court ballets in France under the Ancien Régime (1581-1682) - Couto, Clara Rodrigues (Revista Brasileira de Estudos da Presença, 2021)
This article seeks to understand the theoretical formulations that throughout the 17th century systematized court ballet as an art, a term defined at the time as a set of precepts and rules. After a brief discussion about the first dance manuals produced in modern Europe, we analyze the treatises, discourses and librettos that addressed ballet composition. From the works of Beaujoyeulx, Saint-Hubert, Marolles, De Pure and Ménestrier, among others, it is possible to appreciate the erudite principles and precepts that guided the practice of ballet composition in France under the Ancien Régime, as well as the inclusion of dance and ballet in the domain of written production and literate culture.